An anatolian folk game related to rain prayers: "Çömçeli gelin" - Şimşek, Esma (My University, 2003)
Human being who considered natural disasters as God's revenge, used religious services or rites. When the examples of folk culture, from mitology to legend, are investigated it is seen that they are basically a fight and desire against the unknown powers of the nature. Practices performed for rain prayer are among one of them. Anatolian people, most of whom were farmers, prayed God in dry (arid) times in various rites to provide rain. We will dealth with only the game of "çömçeli gelin/bride with ladle". The legend, it's relation with Old Turkish belief, it's position in traditional games, it's evaluation as a rite and phrases and words in the game will be given comperatively.
Anadolu'da ya?mur duasina ba?li olarak oynanan bi?r oyun: "Çömçeli? geli?n"
Keywords: Belief; Game ceremony; Prayer; Rain; Rite